immunopathological study of the fungus cryptococcus neoformans in mice: 1Mahmood F.A and 2Alwan M.J - Mahmood, F. A . (The Iraqi Journal of Veterinary Medicine, 2019)
The study aimed to investigate the effect of cryptococcal sonicated antigen and chitosan on the infection with this fungus which isolated from human skin lesions. Isolate of Cryptococcus neoformans was used to prepare the sonicated antigen, also 60 white mice from both sexes, at average age 8-10 weeks were getted and divided randomly into 4 groups equally and treated as following: First group: fifteen mice were immunized with 0.5ml of whole sonicated Ags(Wsc Ag) (protein concentration14mg/ml) subcutaneous two doses, one week interval.Second group: fifteen mice were fed diet supplemented with chitosan 1g/kg diet for 6 weeks.Third group: Mice were immunized as 1st group and at the same time fed diet supplemented with chitosan as 2nd group. Fourth group: Mice, which seted as control positive group. At day 28-30 post-immunization, delayed hypersensitivity and indirect passive haemagglutination tests were done, then 1st, 2nd, 3rd and 4th groups were administrated intraperitoneally with 0.3 ml of fungal suspension containing 1X107 fungal cells, all animals were sacrificed at day 30 post-infection. The results showed that the immunized animals and fed diet containing chitosan had values of delayed hypersensitivity test(1.99±0.02 at 24hours and 2.11±0.03 at 48 hours)and value of antibodies(160±29.6) higher than that of immunized animals only(1.75±0.03 at 24 hours and 1.81±0.03 at 48 hours)and value of antibodies(136±28.2).The immunized animals with whole sonicated cryptococcal antigens (1st group) expressed high values of delayed type hypersensitivity and high levels of Abs titer, as well as the chitosan stimulate the immune system in the second group and the best results of immunization were getted in the third group while all animals of control positive(fourth group) were died at the first week post-infection. The current study showed that all the non-immunized and infected animals of the fourth group were died during the first 2 weeks post-infection with severe fungal cells isolated from internal organs and severe suppurative inflammatory reaction in the examined organs during early stage of infection with granulomatous lesions appear at day 14 post-infection while no mortality rate was seen in animal fed diet supplement with chitosan with or without immunization(2nd and 3rd groups) moderate fungal isolation and granulomatous lesions were recorded in the examined organs of animals sacrificed at day 30 post-infection while the immunized animals and fed diet containing chitosan showed that there is no fungal isolation and nor fungal cells in the histological sections with few histological degeneration and small granulomatous lesions and sometimes absence of them in the examined organs. It concluded that cryptococcal sonicated antigen and chitosan have important role in protective immunity against C.neoformans infection.